Intensi Berwirausaha Generasi Muda Di Lodtunduh Ubud Dalam Era E-Busines - Ida Nyoman Basmantra; I Gede Adhi Prasetya Bandem; Ni Wayan Widhiasthini (Eqien - Jurnal Ekonomi dan Bisnis, 2023)
In today's era, humans use technology because they have reason. With their minds, humans want to get out of a problem, they want to live a better, safer, and easier life. One of the businesses that can be done in today's technological advances is e-business. This study focuses on entrepreneurship which aims to determine the Entrepreneurial Intentions of the Young Generation in Lodtunduh Ubud. The intervention is viewed from several variables such as: Digital Literacy, Self-Efficacy, and Environment in the context of the E-Business era. The population in this research was 109 and the sample used was 86 respondents. This research method is quantitative. The data collection technique used is a questionnaire survey and observation. With this research, it is hoped that this research can add and broaden the reader's insight regarding the Entrepreneurial Intentions of the Young Generation in Lodtunduh Ubud in the E-Business era.